Strangers in a strange land: work experiences of foreign nurses in Parma’s territory - Vesperoni, Pietro; Masera, Giuliana (Acta Biomedica Atenei Parmensis, 2015)
Purpose. The purpose of this research is to explore, investigate and describe experiences and points of view of foreign nurses working in the area of Parma. We focalize particularly on two areas of interest: negativities and positivities in experiences related to the process of integration into the new working environment. Background. The literature search has revealed that the phenomenon of “nursing immigration” is numerically significant in Italy and more particularly in Emilia Romagna. From studies conducted in other countries (UK, USA, Canada, Australia and Iceland) there are two categories of factors which influence the process of integration of foreign nurses in the new working environment, facilitators and barriers. Method. For this study we followed the phenomenological method . A total of twelve foreign nurses were interviewed in the months of October and November 2013 in the territory of Parma working in various professional fields (medicine, critical care and surgery). We did not impose any structure to interviews so that respondents were free to express their lived experiences spontaneously. All interviews were recorded, transcribed verbatim and analyzed by the method of Giorgi (1970). Results. Results obtained from the analysis of interviews revealed seven themes, divided in positivities and negativities. Positivities are psycho-social support (Italian colleagues, fellow countrymen, patients), opportunities of cultural enrichment, positive work ethic. negativities are difficulty of language and communication, and inequalities racial prejudice, differences in care practices and inadequate opportunities for professional growth related to the Italian working environment. Conclusions. The study concludes by pointing out the importance of the role that foreign nurses can play in our health care system and how the results of this search can help all professionals in the health sector to have a greater understanding of their experiences. This knowledge can make a contribution to the development of new quantitative research in the same area and then to the formation of new strategies for hospitality and support.